Progresses in Solid-State NMR Studies on Carbon Anode Materials for Lithium/Sodium-Ion Batteries - LEI Zhen-yu; LIANG Xin-miao; LEI You-yi; YANG Li; FENG Ji-wen (Chinese Journal of Magnetic Resonance, 2020)
Carbon anode material is a traditional and widely-used anode material for lithium/sodium-ion batteries. However, it still has some drawbacks, such as long charging time and low columbic efficiency. Studying the charging and discharging mechanisms of the carbon anode material will help to solve these problems. Solid-state nuclear magnetic resonance (NMR) is an effective method to study the chemical environment of target atoms in solid materials and structural changes of materials. By measuring high speed magic-angle spinning (MAS) spectrum of 6Li, 7Li and 23Na in lithium/sodium-ion batteries, the structural changes during the process of de-intercalation and coordination between the carbon atoms and Li/Na atoms can be elucidated. The information obtained can provide a sufficient theoretical basis for designing of novel carbon anode materials and improving their electrochemical properties. This paper reviews the application and progresses of solid-state NMR technology in the research of carbon anode materials for lithium/sodium-ion battery.